Organic electrolyte matched with (poly) dicyclopentadiene for use and carbon fiber surface treatment method
By introducing olefin functional groups on the surface of the carbon fiber and using a coupling agent containing thiol group to synthesize the sizing agent, the problem of poor interfacial binding ability between carbon fiber and polydicyclopentadiene is solved, the interface shear strength is significantly improved, and the efficient interface enhancement effect is achieved.
Patent Information
- Application Number
- CN202411921776.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the prior art, the interfacial bonding ability between carbon fiber and polydicyclopentadiene (PDCPD) is poor, resulting in low interfacial shear strength (IFSS), limiting the application of PDCPD resin-based composite materials.
Using an organic electrolyte used to match (poly)bicyclopentadiene, an olefin functional group is introduced on the surface of the carbon fiber through electrochemical reaction, and a sizing agent synthesized simultaneously through a two-step method using a sulfhydryl-containing coupling agent and a film-forming agent to achieve the chemical bond interaction between the carbon fiber surface and PDCPD.
The interface combination capability between carbon fiber and PDCPD is improved, and the interface shear strength (IFSS) is significantly improved, reaching an increase of 50%-130%. It has simple process and low equipment requirements, making it suitable for continuous production.
Smart Images

Figure CN119899127A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon fiber processing, and in particular relates to an organic electrolyte used in matching (poly) dicyclopentadiene and a carbon fiber surface processing method. Background Art
[0002] Polydicyclopentadiene (PDCPD) has the advantages of low moisture absorption, high strength, impact resistance and environmental protection. Its resin matrix viscosity can be as low as 0.1Pa·s, so it is a composite resin matrix with excellent molding ability. However, when the reinforcement of the polydicyclopentadiene matrix is carbon fiber (CF), the interface energy of both is low and lacks effective interaction, so the interface bonding ability is poor, and the interface shear strength (IFSS) is as low as 13MPa (the IFSS of CF and epoxy resin under the same conditions is about 60MPa). Therefore, the interface energy absorption is a shortcoming that restricts the application of CF-reinforced PDCPD resin-based composite materials.
[0003] In order to solve the above technical problems, the patent with publication number CN114478887A in the prior art first uses supercritical swelling treatment, and then uses a silane coupling agent (4-(4-aminophenyl)benzonitrile triethanolsiloxane) to treat the carbon fiber, but the whole set of processes is complicated, especially the supercritical swelling treatment process cannot be applied to the continuous production of carbon fiber. In the patent with publication number TW202138643A, the carbon fiber is acidified and chlorinated, and then norbornene is grafted through an esterification reaction, but the chlorination and esterification processes require anhydrous and oxygen-free conditions, so they are not suitable for continuous production of carbon fiber. In the patent with publication number CN110387115A, the carbon fiber is washed with water and then treated with a silane coupling agent KH570, but the water washing process cannot introduce functional groups on the surface of the carbon fiber that can interact with the silane coupling agent or PDCPD. The patent with publication number CN113400683A uses a secondary infusion method to prepare composite materials, but the secondary infusion process cannot introduce functional groups that can interact with silane coupling agents or PDCPD on the surface of carbon fibers. The patent with publication number CN116003943A improves the interaction with fibers by introducing epoxy resin into DCPD resin, but this loses the advantages of low moisture absorption, high strength and impact resistance of PDCPD. The patents with publication numbers CN106366300A, CN106749949A, CN106749947A, CN106589250A, CN104448084A and CN102827318A all use silane coupling agents (such as KH570) to modify glass fibers to improve their interface bonding and ability with PDCPD, but the surface of glass fibers is rich in hydroxyl groups that can interact with silane coupling agents to produce chemical bonds, which is a characteristic that carbon fibers do not have. In addition, the amino, hydroxyl, epoxy and other functional groups provided by conventional silane coupling agents cannot produce strong interactions with PDCPD, which is equivalent to improving the interfacial performance. KH570 can provide aliphatic ethylene functional groups, but the crosslinking mechanism of DPCD is ring-opening metathesis polymerization, which is different from aliphatic ethylene functional groups. Therefore, the chemical bond ability of KH570 and DCPD is limited, which leads to limited interface improvement ability. The patent with publication number CN116063823A uses norbornene-based silane coupling agent to treat CF. Norbornene has the same crosslinking mechanism as DCPD, both of which are ring-opening metathesis polymerization, but it still fails to improve the binding problem of silane coupling agent and CF. Summary of the invention
[0004] The present invention aims to solve the technical problems in the prior art and provide an organic electrolyte and a carbon fiber surface treatment method that can be applied to the continuous production of carbon fibers, wherein the coupling agent has a chemical bond interaction with the carbon fiber surface, the coupling agent has a chemical bond interaction with the carbon fiber surface PDCPD, and the chemical bond interaction is efficient and easy to construct to match the use of (poly) dicyclopentadiene.
[0005] In order to solve the above technical problems, the technical solutions of the present invention are as follows:
[0006] An organic electrolyte used in matching (poly) dicyclopentadiene, the structural formula of which is as follows:
[0007]
[0008] Wherein, R is one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures; n is any integer between 0 and 5 (including 0 and 5);
[0009] -H, -Ph.
[0010] In the above technical solution, preferably, the organic electrolyte is obtained by reacting an olefin derivative of aniline, nitrite tetrafluoroborate, an anti-crosslinking agent, and acetonitrile or toluene, and the synthesis reaction formula is as follows:
[0011]
[0012] A carbon fiber surface treatment method comprises the following steps:
[0013] The carbon fiber surface treatment method is divided into two stages;
[0014] Stage ① Olefin enrichment on carbon fiber surface:
[0015] After carbonizing the carbon fiber, the surface is electrochemically treated;
[0016] The electrochemical treatment process is as follows: the carbon fiber is used as the cathode, and the electrolyte required for electrochemical reduction includes an organic electrolyte and a supporting electrolyte;
[0017] The organic electrolyte is obtained by reacting an olefin derivative of aniline, nitrite tetrafluoroborate, an anti-crosslinking agent, and acetonitrile or toluene, and the synthesis reaction formula is as follows:
[0018]
[0019] Wherein, R is one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures; n is any integer between 0 and 5 (including 0 and 5);
[0020] -H, -Ph
[0021] Stage 2 Carbon fiber sizing:
[0022] Sizing the electrochemically treated carbon fiber;
[0023] The sizing agent required for the carbon fiber sizing treatment includes a coupling agent and a film-forming agent, wherein the coupling agent is recorded as component 1 and the film-forming agent is recorded as component 2;
[0024] The sizing agent is synthesized simultaneously from dicyclopentadiene and a sulfide compound by a two-step method, and the reaction system is directly used to prepare a solution-type or emulsion-type sizing agent after filtration;
[0025] The structural formula of the dicyclopentadiene is as follows:
[0026]
[0027] The structural formula of the thioether compound is as follows:
[0028]
[0029] Wherein, the three R1 groups are the same or different, and are one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures, and at least one of the three R1 is not a hydrogen atom; n1 is any integer between 0 and 5 (including 0 and 5);
[0030] -H,
[0031] The component 1 is a mixture of the following substances;
[0032]
[0033] Wherein, the three R2 groups are the same or different, and are one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures, and at least one of the three R2 is not a hydrogen atom; n2 is any integer between 0 and 5 (including 0 and 5);
[0034] -H,
[0035] The component 2 is a mixture of the following substances;
[0036]
[0037] The sizing agent further includes: a coupling catalyst, and the coupling catalyst is recorded as component 3.
[0038] In the above technical solution, preferably, the electrolyte required for electrochemical reduction is prepared by: dissolving the anti-crosslinking agent in acetonitrile or toluene, then completely dissolving the olefin derivative of aniline in the acetonitrile or toluene solution of the anti-crosslinking agent, then slowly dripping a saturated tetrafluoroborate nitrite solution into the above solution, reacting for 15 minutes, and finally dissolving the supporting electrolyte in the reaction system to obtain the electrolyte required for electrochemical reduction;
[0039] The electrolyte required for electrochemical reduction has: an organic electrolyte molar concentration of 1-10 mM; a supporting electrolyte molar concentration of 1-3 mM; an anti-crosslinking agent molar concentration of 0.01-0.1 mM;
[0040] The supporting electrolyte is tetrabutylammonium tetrafluoroborate;
[0041] The anti-crosslinking agent is phenol, catechol, 2,4-dinitrophenol, 2,6-dinitro-p-cresol or 2,6-di-tert-butyl-4-benzylidenecyclohexa-2,5-dienone;
[0042] The potential difference of the electrochemical reaction is 0.5V;
[0043] The molar ratio of component 1 to component 2 in the sizing agent component is 1:0.8-1:5.
[0044] In the above technical solution, preferably, in the first step of obtaining the sizing agent:
[0045] The molar ratio of the reactant dicyclopentadiene to the sulfide compound is 2:1 to 5:1;
[0046] The solvent is toluene, and the concentration of dicyclopentadiene is 0.1-2.0 mol / L;
[0047] Catalyst 1 is aluminum chloride, aluminum bromide, trifluoroacetic acid or methanesulfonic acid;
[0048] The reaction temperature is 60-200°C, and the synthesis reaction time is 2-7h.
[0049] In the above technical solution, preferably, in the second step of obtaining the sizing agent:
[0050] Catalyst 2 is Raney Ni;
[0051] The reaction temperature is 40-60°C;
[0052] The reaction time is 10-15h;
[0053] The pressure of the reaction system is 0.1-0.2MPa.
[0054] In the above technical scheme, it is preferred that when component 3 requires high temperature initiation or light initiation, a one-step or two-step sizing method for carbon fiber surface treatment is adopted, or an emulsion sizing method or a solution sizing method is adopted; when component 3 requires room temperature initiation, a two-step emulsion sizing method for carbon fiber surface treatment is adopted.
[0055] In the above technical solution, it is further preferred that component 3 is dibenzoyl peroxide and dimethylaniline, or azobisisobutyl cyanide, or dibenzoyl peroxide, or benzoin dimethyl ether, or benzophenone and azobisisobutyl cyanide.
[0056] In the above technical scheme, preferably, when component 3 is azobisisobutyl cyanide, dibenzoyl peroxide, benzoin dimethyl ether, or benzophenone and azobisisobutyl cyanide, a one-step emulsion sizing or one-step solution sizing carbon fiber surface treatment method is adopted;
[0057] The above-mentioned one-step emulsion sizing carbon fiber surface treatment method specifically comprises the following steps:
[0058] a. preparing a mixture of component 1 and component 2 into an emulsion, recorded as emulsion 1;
[0059] b. preparing component 3 into an emulsion, recorded as emulsion 2;
[0060] c. The emulsion 1, emulsion 2, antistatic agent, lubricant and deionized water in a mass ratio of 5 to 20: 0.5 to 10: 0.1 to 0.5: 0.2 to 0.8: the remainder, the remainder is the mass of deionized water, a total of 100 parts by mass, configured as an emulsion sizing agent;
[0061] d. When component 3 is azobisisobutyl cyanide or dibenzoyl peroxide, the carbon fiber is sized and dried at 100-150°C before being rolled up; when component 3 is benzoin dimethyl ether or benzophenone and azobisisobutyl cyanide, the carbon fiber is first sized and then treated with ultraviolet rays, and then dried at 100-150°C before being rolled up;
[0062] The above one-step solution sizing carbon fiber surface treatment method specifically comprises the following steps:
[0063] a. Component 1 + component 2 (containing no solvent), component 3, an antistatic agent, a lubricant and an organic solvent in a mass ratio of 1 to 2: 0.01 to 0.1: 0.1 to 0.5: 0.2 to 0.8: the remainder, the remainder being the mass of the organic solvent, a total of 100 parts by mass, is configured as a solution-type sizing agent; further preferably, the organic solvent is acetonitrile or toluene;
[0064] b. When component 3 is azobisisobutyl cyanide or dibenzoyl peroxide, the carbon fiber is sizing and then dried at 120-150°C before being rolled up; when component 3 is benzoin dimethyl ether or benzophenone and azobisisobutyl cyanide, the carbon fiber is first sizing and then treated with ultraviolet rays, and then dried at 120-150°C before being rolled up.
[0065] In the above technical scheme, it is preferred that when component 3 is dibenzoyl peroxide and dimethylaniline, or azobisisobutyl cyanide, or dibenzoyl peroxide, or benzoin dimethyl ether, or benzophenone and azobisisobutyl cyanide, a two-step emulsion sizing method for treating the surface of carbon fiber is used;
[0066] The two-step emulsion sizing carbon fiber surface treatment method specifically comprises the following steps:
[0067] a. preparing a mixture of component 1 and component 2 into an emulsion, recorded as emulsion 1;
[0068] b. preparing component 3 into an emulsion, recorded as emulsion 2;
[0069] c. The emulsion 1, antistatic agent, lubricant and deionized water in a mass ratio of: 5 to 20: 0.1 to 0.5: 0.2 to 0.8: the remainder, the remainder is the mass of deionized water, a total of 100 parts by mass, configured as an emulsion sizing agent;
[0070] d. The carbon fiber is first sized with emulsion 2, and then blown dry until no liquid drops after sizing. The emulsion sizing obtained in step c, when component 3 is dibenzoyl peroxide and dimethylaniline, azobisisobutyl cyanide or dibenzoyl peroxide, the carbon fiber is sizing and then dried at 100-150°C and then rolled up; when component 3 is benzoin dimethyl ether or benzophenone and azobisisobutyl cyanide, the carbon fiber is first sizing and then treated with ultraviolet rays, and then dried at 100-150°C and then rolled up.
[0071] The beneficial effects of the present invention are:
[0072] The present invention provides an olefin-rich organic electrolyte matched with (poly)dicyclopentadiene, and designs a special electrolyte, which can introduce more olefin functional groups with higher reaction activity on the surface of carbon fiber through electrochemical reaction, providing more abundant sites for coupling with the sizing agent through click chemical reaction during the sizing process.
[0073] The carbon fiber surface treatment method provided by the present invention has the following advantages:
[0074] 1. The present invention first uses an olefin-rich organic electrolyte to introduce a larger number of olefin functional groups with higher reaction activity on the surface of carbon fiber. The carbon fiber surface olefin-rich method can be achieved using conventional carbon fiber production equipment (electrochemical oxidation tank), which is one of the outstanding features of the present invention.
[0075] 2. A series of coupling agents containing mercapto groups (one of the components of the sizing agent) is the second outstanding feature of the present invention.
[0076] 3. The present invention is based on the process of sulfhydryl protection and deprotection, and the two-step simultaneous synthesis of a sulfhydryl-containing coupling agent and a film-forming agent (one of the sizing agent components), which is the third outstanding feature of the present invention.
[0077] 4. The fourth outstanding substantial feature of the present invention is the method of using the coupling agent and the film-forming agent to prepare a special sizing agent and treat the surface of the carbon fiber to achieve in-situ chemical bonding with the surface of the carbon fiber during the sizing process.
[0078] 5. The thiol-containing coupling agent used in the treatment method of the present invention can produce chemical bond interactions with the surface of olefin-rich carbon fibers through click chemistry reactions. The reaction rate is fast and the reaction efficiency is high. During the sizing process, functional groups that can cross-link with DCPD can be introduced on the surface of the carbon fibers through carbon-sulfur bonds, which is one of the significant advances of the present invention.
[0079] 6. The coupling agent and film-forming agent used in the present invention are simultaneously synthesized by a two-step method. After the first step reaction, no separation or solvent collection is required. Only water washing treatment is required to carry out the second step reaction. After the second step reaction, no separation or solvent collection is required. Only filtering treatment is required to prepare a sizing agent. It has industrialization capability, low equipment requirements and is green and environmentally friendly, which is the second significant improvement of the present invention.
[0080] 7. The carbon fiber surface treatment method of the present invention does not contain acidification, chlorination, esterification and other anhydrous and oxygen-free reaction conditions, nor does it require high temperature and high pressure reaction conditions such as supercritical treatment. It can be achieved in an atmospheric environment using conventional carbon fiber production equipment, and has low requirements for equipment and personnel. This is the third significant improvement of the present invention.
[0081] 8. The carbon fiber surface treatment method of the present invention improves the IFSS of commercially sized CF by 50%-130%, which is the fourth significant improvement of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0082] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0083] Figure 1 Schematic diagram of the chemical structure of the olefin derivative 1 of aniline.
[0084] Figure 2 Schematic diagram of the chemical structure of the olefin derivative 2 of aniline.
[0085] Figure 3 Schematic diagram of the chemical structure of the olefin derivative 3 of aniline.
[0086] Figure 4 Schematic diagram of the chemical structure of the olefin derivative 4 of aniline.
[0087] Figure 5Schematic diagram of the chemical structure of the olefin derivative 5 of aniline.
[0088] Figure 6 Schematic diagram of the chemical structure of the olefin derivative 6 of aniline.
[0089] Figure 7 Schematic diagram of the chemical structure of the olefin derivative 7 of aniline. DETAILED DESCRIPTION
[0090] The inventive idea of the present invention is: in order to solve the technical problems existing in the prior art, it is necessary to construct an interface phase that can produce chemical bonds with both carbon fiber and DCPD, so three interface enhancement strategies are generated, which can be divided into resin first and fiber second, chemical bonds are produced at the same time, and fiber first and resin second according to the order of the interface phase and the two sides to produce chemical bonds. The construction method of resin first and fiber second requires the overall modification of the resin matrix, which is not only costly, but also easy to damage the advantageous characteristics of the resin matrix itself; the strategy of producing chemical bonds at the same time is usually implemented during the processing process, DCPD usually has a low viscosity, and it is easy to dissolve the unstable interface phase during the preforming process; the strategy of CF first in resin can be achieved through the sizing process, which is easy to operate and has low dependence on equipment and personnel. Therefore, the present invention adopts: first, the electrochemical oxidation tank of conventional carbon fiber production equipment is used to construct a large number of active functional groups on the surface of carbon fiber through electrochemical reaction, and then synthesize a sizing agent coupling agent that can react efficiently with this functional group. The coupling agent can introduce a functional group that can produce covalent bonds with DCPD through ring opening polymerization, and finally realize the chemical bond combination of carbon fiber-sizing agent-resin matrix.
[0091] The present invention is implemented in two steps: Phase ① Olefin enrichment of the carbon fiber surface: It can be implemented using the conventional electrochemical oxidation tank in the carbon fiber production line. The present invention first develops a special olefin-enriched organic electrolyte and designs a special electrolyte. Through electrochemical reactions, more olefin functional groups with higher reaction activity can be introduced on the surface of the carbon fiber, providing more abundant sites for coupling with the sizing agent through click chemical reactions during the sizing process; Phase ② Carbon fiber sizing: The present invention designs and develops a highly active coupling agent, which can interact with the olefin functional groups constructed in the phase ① process through conditional click chemical reactions to build chemical bonds, while retaining part of the dicyclo / tricyclopentadiene structure, that is, retaining the ability to cross-link with the DCPD matrix. Based on this, the present invention further optimizes the coupling agent synthesis process, so that the two most important components of the sizing agent, the coupling agent (component 1) and the film-forming agent (component 2), are synthesized simultaneously by a two-step method, and the first step reaction (hereinafter referred to as reaction 1) does not need to be separated or solvent-collected, and only water washing treatment is required to carry out the second step reaction (hereinafter referred to as reaction 2), and the second step reaction does not need to be separated or solvent-collected, and the reaction system can be directly used to configure a solution-type or emulsion-type sizing agent after filtration. Finally, the present invention optimizes the introduction strategy of the coupling catalyst (component 3) to maximize the reaction efficiency of the carbon fiber and the sizing agent layer.
[0092] The invention is simple to operate, energy-saving and environmentally friendly, has low requirements on equipment, has good interface enhancement effect, can realize batch production of sizing agents, and can realize batch production of special carbon fibers.
[0093] The present invention first provides an organic electrolyte matched with (poly) dicyclopentadiene, and its structural formula is as follows:
[0094]
[0095] Wherein, R is one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures; n is any integer between 0 and 5 (including 0 and 5);
[0096] -H, -Ph.
[0097] Preferably, the organic electrolyte is obtained by reacting an olefin derivative of aniline, nitrite tetrafluoroborate, an anti-crosslinking agent, and acetonitrile or toluene, and the synthesis reaction formula is as follows:
[0098]
[0099] The present invention also provides a carbon fiber surface treatment method, which is achieved by the following steps:
[0100] Stage ① Olefin enrichment on carbon fiber surface:
[0101] (1) dissolving the anti-crosslinking agent in acetonitrile or toluene, then adding the olefin derivative of aniline (reactant), and stirring until completely dissolved; dissolving nitrite tetrafluoroborate (NOBF4) in a minimum amount of acetonitrile or toluene, and then slowly dripping it into the above-mentioned olefin derivative solution of aniline, reacting for 15 minutes, adding a supporting electrolyte to obtain the electrolyte required for electrochemical reduction, and injecting the electrolyte required for electrochemical reduction into an electrochemical oxidation tank for standby use.
[0102] The obtained electrolyte includes an organic electrolyte and a supporting electrolyte;
[0103] The organic electrolyte is obtained by reacting an olefin derivative of aniline, tetrafluoroborate nitrite, an anti-crosslinking agent, and acetonitrile or toluene. The synthesis reaction formula is as follows:
[0104]
[0105] Wherein, R is one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures; n is any integer between 0 and 5 (including 0 and 5);
[0106] -H, -Ph
[0107] (2) The carbon fiber primary fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reduction reaction with a potential difference of 0.5 V. After the reaction, the fiber is washed with water and dried before being processed in stage ②.
[0108] Stage 2 Carbon fiber sizing:
[0109] Sizing the electrochemically treated carbon fiber;
[0110] The sizing agent required for the carbon fiber sizing treatment includes a coupling agent and a film-forming agent, wherein the coupling agent is recorded as component 1 and the film-forming agent is recorded as component 2;
[0111] The sizing agent is synthesized simultaneously from dicyclopentadiene and a sulfide compound by a two-step method, and the reaction system is directly used to prepare a solution-type or emulsion-type sizing agent after filtration;
[0112] The structural formula of the dicyclopentadiene is as follows:
[0113]
[0114] The structural formula of the thioether compound is as follows:
[0115]
[0116] Wherein, the three R1 groups are the same or different, and are one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures, and at least one of the three R1 is not a hydrogen atom; n1 is any integer between 0 and 5 (including 0 and 5);
[0117] -H,
[0118] The component 1 is a mixture of the following substances;
[0119]
[0120] Wherein, the three R2 groups are the same or different, and are one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures, and at least one of the three R2 is not a hydrogen atom; n2 is any integer between 0 and 5 (including 0 and 5);
[0121] -H,
[0122] The component 2 is a mixture of the following substances;
[0123]
[0124] The sizing agent further comprises: a coupling catalyst, wherein the coupling catalyst is recorded as component 3;
[0125] The sizing agent is synthesized by two-step reaction, and the synthesis reaction formula is as follows:
[0126]
[0127] In the synthetic reaction formula, the composition and chemical structure of the intermediate are as follows:
[0128]
[0129] The above R1 group is consistent with the above definition and will not be repeated here;
[0130] The sizing process specifically includes the following steps:
[0131] (1) Add DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject an organic solvent, and stir to fully dissolve DCPD; add catalyst 1 and stir evenly; dissolve the sulfide compound in the organic solvent and add it dropwise to the reactor; heat to a specified temperature, and cool to room temperature after the reaction is completed; filter to remove residue, wash the filtrate with water three times, and obtain a mixed solution of a specific ratio of the intermediate and component 2 after separation;
[0132] (2) adding a catalytic amount of Raney Ni catalyst 2 to a mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the high pressure in the reactor, heating to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering to remove the residue after the reaction is completed, and obtaining a mixed solution of component 1 and component 2 (hereinafter referred to as the stock solution); the synthesis reaction formula is shown in the above reaction formula;
[0133] (3) The stock solution can be diluted and then added with component 3, an antistatic agent and a lubricant to be used directly as a one-step solution sizing agent, or an emulsifier and deionized water can be added to prepare emulsion 1 for standby use;
[0134] (4) dissolving component 3 in an organic solvent, adding an emulsifier and deionized water to prepare emulsion 2;
[0135] (5) According to different sizing methods, a one-step solution sizing agent, a one-step emulsion sizing agent or a two-step emulsion sizing agent is respectively prepared; the surface modification of carbon fiber is achieved by one-step solution sizing, one-step emulsion sizing or two-step emulsion sizing, and the coupling agent can efficiently interact with CF by chemical bonds during the sizing (including drying) process, while retaining part of the dicyclo / tricyclopentadiene structure.
[0136] Preferably, in the above-mentioned stage ① step (1), the olefin content in the olefin derivative of aniline (reactant) is greater than the amino content;
[0137] Furthermore, the electrolyte composition required for electrochemical reduction in the above-mentioned stage ① step (1) is: organic electrolyte molar concentration 1-10mM; supporting electrolyte molar concentration 1-3mM; anti-crosslinking agent molar concentration 0.01-0.1mM;
[0138] Furthermore, in the above-mentioned stage ① step (1), the supporting electrolyte is tetrabutylammonium tetrafluoroborate;
[0139] Furthermore, in the above-mentioned stage ① step (1), the anti-crosslinking agent is: phenol, catechol, 2,4-dinitrophenol, 2,6-dinitro-p-cresol or 2,6-di-tert-butyl-4-benzylidenecyclohexa-2,5-dienone;
[0140] Furthermore, in the above-mentioned stage ② step (1), the molar ratio of the reactant dicyclopentadiene to the sulfide compound is 2:1 to 5:1;
[0141] Furthermore, the organic solvent used in the above-mentioned stage ② step (1) is toluene, and the concentration of dicyclopentadiene is 0.1-2.0 mol / L, and more preferably 0.1-1.0 mol / L;
[0142] Furthermore, the catalyst used in the above-mentioned stage ② step (1) is aluminum chloride, aluminum bromide, trifluoroacetic acid or methanesulfonic acid;
[0143] Furthermore, in the above-mentioned stage ② step (1), the temperature of the synthesis reaction of component 1 and component 2 is 60-200°C;
[0144] Furthermore, the time for the synthesis reaction of component 1 and component 2 in step (1) of the above stage ② is 2-7 hours;
[0145] Furthermore, in the above-mentioned stage ② step (2), the molar ratio of component 1 to component 2 in the stock solution is 1:0.8-1:5; catalyst 2 is Raney Ni; the reaction temperature is 40-60° C., the reaction time is 10-15 h, and the reaction system pressure is 0.1-0.2 MPa;
[0146] Furthermore, the mass fraction of component 1 + component 2 in the emulsion 1 prepared in the above stage ② step (3) is 10% to 20%;
[0147] Preferably, the oil-water ratio of the emulsion 1 prepared in the above-mentioned stage ② step (3) is 1:1 to 1:2;
[0148] Furthermore, in the above-mentioned stage ② step (4), component 3 is: dibenzoyl peroxide + dimethylaniline, azobisisobutyl cyanide, dibenzoyl peroxide, benzoin dimethyl ether or benzophenone + azobisisobutyl cyanide;
[0149] Furthermore, the mass fraction of component 3 in the emulsion 2 prepared in the above stage ② step (4) is 10% to 20%;
[0150] Preferably, the oil-water ratio of the emulsion 2 prepared in the above-mentioned stage ② step (4) is 1:1 to 1:2;
[0151] Furthermore, in the above-mentioned stage ② step (5), when component 3 is azobisisobutyl cyanide, dibenzoyl peroxide, benzoin dimethyl ether or benzophenone + azobisisobutyl cyanide, a one-step emulsion sizing, one-step solution sizing or two-step emulsion sizing method for treating the carbon fiber surface can be adopted;
[0152] Furthermore, in the above-mentioned stage ② step (5), when component 3 is dibenzoyl oxide + dimethylaniline, only the carbon fiber surface treatment method of two-step emulsion sizing can be used;
[0153] Furthermore, the carbon fiber surface treatment method of one-step emulsion sizing in step (5) of the above stage ② is specifically as follows:
[0154] ① Prepare an emulsion type sizing agent by mixing emulsion 1, emulsion 2, an antistatic agent, a lubricant and deionized water in a mass ratio of 5-20:0.5-10:0.1-0.5:0.2-0.8: the remainder (a total of 100);
[0155] ② When component 3 is azobisisobutyl cyanide or dibenzoyl peroxide, the carbon fiber is sizing and then dried at 100-150°C before being rolled up; when component 3 is benzoin dimethyl ether or benzophenone + azobisisobutyl cyanide, the carbon fiber is first sizing and then treated with ultraviolet rays, and then dried at 100-150°C before being rolled up.
[0156] Furthermore, the surface treatment method of carbon fiber by one-step solution sizing in the above-mentioned stage ② step (5) is specifically as follows:
[0157] ① Component 1 + component 2 (without solvent), component 3, antistatic agent, lubricant and organic solvent are configured into a solution-type sizing agent in a mass ratio of 1-2: 0.01-0.1: 0.1-0.5: 0.2-0.8: the remainder (a total of 100);
[0158] ② When component 3 is azobisisobutyl cyanide or dibenzoyl peroxide, the carbon fiber is sizing and then dried at 120-150°C before being rolled up; when component 3 is benzoin dimethyl ether or benzophenone + azobisisobutyl cyanide, the carbon fiber is first sizing and then treated with ultraviolet rays, and then dried at 120-150°C before being rolled up.
[0159] Furthermore, the carbon fiber surface treatment method of the two-step emulsion sizing in the above stage ② step (5) is specifically as follows:
[0160] ① Prepare an emulsion sizing agent by mixing emulsion 1, an antistatic agent, a lubricant and deionized water in a mass ratio of 5-20:0.1-0.5:0.2-0.8: the remainder (a total of 100);
[0161] ② The carbon fiber is first sized with emulsion 2, then blown dry until no liquid drops, and then sized with the emulsion obtained in ①. When component 3 is dibenzoyl peroxide + dimethylaniline, azobisisobutyl cyanide, or dibenzoyl peroxide, the carbon fiber is dried at 100-150°C after sizing and then rolled up; when component 3 is benzoin dimethyl ether or benzophenone + azobisisobutyl cyanide, the carbon fiber is first sized and then treated with ultraviolet rays, and then dried at 100-150°C and rolled up.
[0162] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0163] The amount of catalyst used in the following examples can be based on the conventional catalytic amount in the art. The antistatic agent, lubricant and emulsifier used can be any reagent that can achieve their functions, and the present invention has no special restrictions on their respective types.
[0164] Embodiment 1:
[0165] Phase 1:
[0166] (1) Dissolve 0.01 mM phenol in toluene, then add 1 mM aniline olefin derivative 1 (chemical structure as shown in Figure 1 As shown), stir until completely dissolved; dissolve 1 mM nitrosoborate tetrafluoroborate in a minimum amount of toluene, then slowly drip into the above-mentioned olefin derivative 1 solution of aniline, react for 15 minutes, add 1 mM tetrabutylammonium tetrafluoroborate to obtain the electrolyte required for electrochemical reduction, and inject the electrolyte required for electrochemical reduction into the electrochemical oxidation tank for standby use.
[0167] (2) The raw carbon fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reaction at a potential difference of 0.5 V. After the reaction, it is washed with water and dried before being processed in stage ②.
[0168] Phase 2:
[0169] (1) Add 132.2 g of DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject 7 L of toluene, and stir to fully dissolve the DCPD; add a catalytic amount of aluminum chloride and stir evenly; dissolve 62.1 g of thioanisole in 3 L of toluene and add dropwise to the reactor; heat to 60° C., react for 2 h, and cool to room temperature after the reaction is completed; filter to remove residue, wash the filtrate with water three times, and separate to obtain a mixed solution of the intermediate and component 2 with a molar ratio of 1:0.8;
[0170] (2) adding a catalytic amount of Raney Ni catalyst to the mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the pressure in the reactor at 0.1 MPa, heating to 40° C. for 10 h to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering and removing the residue after the reaction to obtain a mixed solution of component 1 and component 2 (hereinafter referred to as the stock solution);
[0171] (3) After the stock solution is diluted, azobisisobutyl cyanide, an antistatic agent and a lubricant are added to prepare a one-step solution sizing agent, and component 1 + component 2 (without solvent), azobisisobutyl cyanide, an antistatic agent, a lubricant and toluene are prepared in a mass ratio of 1:0.01:0.1:0.2: the remainder (a total of 100) to prepare a solution sizing agent;
[0172] (4) After sizing, the carbon fiber is dried at 120°C and then rolled up;
[0173] (5) The IFSS of carbon fiber and PDCPD after sizing is 18 MPa, and the IFSS of commercially sized CF and PDCDP is 12 MPa.
[0174] Embodiment 2:
[0175] Phase 1:
[0176] (1) Dissolve 0.1 mM catechol in toluene, then add 10 mM olefin derivative 2 of aniline (chemical structure as shown in Figure 2 As shown), stir until completely dissolved; dissolve 10mM nitrosoborate tetrafluoroborate in a minimum amount of toluene, then slowly drip into the above-mentioned olefin derivative 2 solution of aniline, react for 15 minutes, add 3mM tetrabutylammonium tetrafluoroborate to obtain the electrolyte required for electrochemical reduction, and inject the electrolyte required for electrochemical reduction into the electrochemical oxidation tank for standby use.
[0177] (2) The raw carbon fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reaction at a potential difference of 0.5 V. After the reaction, it is washed with water and dried before being processed in stage ②.
[0178] Phase 2:
[0179] (1) Add 2644 g DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject 7 L toluene, and stir to fully dissolve DCPD; add a catalytic amount of aluminum bromide and stir evenly; dissolve 552 g benzyl methyl sulfide in 3 L toluene and add dropwise to the reactor; heat to 200 ° C, react for 7 hours, and cool to room temperature after the reaction is completed; filter to remove residue, wash the filtrate with water three times, and separate to obtain a mixed solution of the intermediate and component 2 with a molar ratio of 1:5;
[0180] (2) adding a catalytic amount of Raney Ni catalyst to the mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the pressure in the reactor at 0.2 MPa, heating to 60° C. for 15 h to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering and removing the residue after the reaction to obtain a mixed solution of component 1 and component 2 (hereinafter referred to as the stock solution);
[0181] (3) After the stock solution is diluted, dibenzoyl peroxide, an antistatic agent and a lubricant are added to prepare a one-step solution sizing agent, and component 1 + component 2 (without solvent), dibenzoyl peroxide, antistatic agent, lubricant and toluene are prepared in a mass ratio of 2:0.1:0.5:0.8: the remainder (a total of 100) to prepare a solution sizing agent;
[0182] (4) After sizing, the carbon fiber is dried at 150°C and then rolled up;
[0183] (5) The IFSS of carbon fiber and PDCPD after sizing is 27.6MPa, and the IFSS of commercially sized CF and PDCDP is 12MPa.
[0184] Embodiment 3:
[0185] Phase 1:
[0186] (1) Dissolve 0.1 mM 2,4-dinitrophenol in toluene, and then add 10 mM olefin derivative 3 of aniline (chemical structure as shown in Figure 3 As shown), stir until completely dissolved; dissolve 10mM nitrosoborate tetrafluoroborate in a minimum amount of toluene, then slowly drip into the above-mentioned olefin derivative 3 solution of aniline, react for 15 minutes, add 3mM tetrabutylammonium tetrafluoroborate to obtain the electrolyte required for electrochemical reduction, and inject the electrolyte required for electrochemical reduction into the electrochemical oxidation tank for standby use.
[0187] (2) The raw carbon fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reaction at a potential difference of 0.5 V. After the reaction, it is washed with water and dried before being processed in stage ②.
[0188] Phase 2:
[0189] (1) Add 2644 g of DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject 7 L of toluene, and stir to fully dissolve the DCPD; add a catalytic amount of trifluoroacetic acid and stir evenly; dissolve 608 g of (2-phenylethyl) methyl sulfide in 3 L of toluene and add dropwise to the reactor; heat to 180° C., react for 5 h, and cool to room temperature after the reaction is completed; filter to remove the residue, wash the filtrate with water three times, and separate the liquids to obtain a mixed solution of the intermediate and component 2 in a molar ratio of 1:5;
[0190] (2) adding a catalytic amount of Raney Ni catalyst to the mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the pressure in the reactor at 0.2 MPa, heating to 60° C. for 15 h to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering and removing the residue after the reaction to obtain a mixed solution of component 1 and component 2 (hereinafter referred to as the stock solution);
[0191] (3) adding toluene to dilute the stock solution to a mass fraction of component 1 + component 2 of 20%, adding deionized water and an emulsifier equal in volume to the organic solution, and preparing emulsion 1 under stirring (the oil-water ratio in emulsion 1 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0192] (4) dissolving benzoin dimethyl ether in toluene (mass fraction of 20%), adding deionized water and emulsifier in an amount equal to the volume of the organic solution, and preparing emulsion 2 under stirring (the oil-water ratio in emulsion 2 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0193] (5) preparing a one-step emulsion sizing agent by mixing emulsion 1, emulsion 2, an antistatic agent, a lubricant and deionized water in a mass ratio of 5:0.5:0.1:0.2: the remainder (a total of 100);
[0194] (6) the carbon fiber is treated with ultraviolet light after being sizing agent prepared by the one-step emulsion sizing agent in step (4), and finally dried at 130° C. and rolled up;
[0195] (7) The IFSS of carbon fiber and PDCPD after sizing is 25 MPa, and the IFSS of commercially sized CF and PDCDP is 12 MPa.
[0196] Embodiment 4:
[0197] Phase 1:
[0198] (1) Dissolve 0.1 mM 2,6-dinitro-p-cresol in toluene, and then add 10 mM olefin derivative 4 of aniline (chemical structure as shown in Figure 4 As shown), stir until completely dissolved; dissolve 10mM nitrosoborate tetrafluoroborate in a minimum amount of toluene, then slowly drip into the above-mentioned olefin derivative 4 solution of aniline, react for 15 minutes, add 3mM tetrabutylammonium tetrafluoroborate to obtain the electrolyte required for electrochemical reduction, and inject the electrolyte required for electrochemical reduction into the electrochemical oxidation tank for standby use.
[0199] (2) The raw carbon fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reaction at a potential difference of 0.5 V. After the reaction, it is washed with water and dried before being processed in stage ②.
[0200] Phase 2:
[0201] (1) Add 2644 g of DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject 7 L of toluene, and stir to fully dissolve the DCPD; add a catalytic amount of methanesulfonic acid and stir evenly; dissolve 664 g of (3-phenylbutyl) methyl sulfide in 3 L of toluene and add dropwise to the reactor; heat to 180° C., react for 5 h, and cool to room temperature after the reaction is completed; filter to remove the residue, wash the filtrate with water three times, and separate the liquids to obtain a mixed solution of the intermediate and component 2 in a molar ratio of 1:5;
[0202] (2) adding a catalytic amount of Raney Ni catalyst to the mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the pressure in the reactor at 0.2 MPa, heating to 60° C. for 15 h to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering and removing the residue after the reaction to obtain a mixed solution of component 1 and component 2 (hereinafter referred to as the stock solution);
[0203] (3) Add toluene to dilute the stock solution to a mass fraction of component 1 + component 2 of 60%, add deionized water and emulsifier twice the volume of the organic solution, and emulsify under stirring. The above emulsion, antistatic agent, lubricant and deionized water are prepared in a mass ratio of 20:0.5:0.8: the remainder (a total of 100) to form emulsion 1;
[0204] (4) dissolving benzoin dimethyl ether in toluene (mass fraction 60%), adding deionized water and an emulsifier twice the volume of the organic solution, and preparing emulsion 2 under stirring (the oil-water ratio in emulsion 2 is 1:2, and the mass fraction of component 1 + component 2 is 20%);
[0205] (5) The carbon fiber is sized with emulsion 1 and then blown dry until no liquid drops fall, then sized with emulsion 2, then treated with ultraviolet light, and finally dried at 130°C and rolled up;
[0206] (6) The IFSS of carbon fiber and PDCPD after sizing is 22 MPa, and the IFSS of commercially sized CF and PDCDP is 12 MPa.
[0207] Embodiment 5:
[0208] Phase 1:
[0209] (1) 0.1 mM 2,6-di-tert-butyl-4-benzylidenecyclohexa-2,5-dienone was dissolved in toluene, and then 10 mM olefin derivative 5 of aniline (chemical structure as shown in Figure 5 As shown), stir until completely dissolved; dissolve 10mM nitrosoborate tetrafluoroborate in a minimum amount of toluene, then slowly drip into the above-mentioned olefin derivative 5 solution of aniline, react for 15 minutes, add 3mM tetrabutylammonium tetrafluoroborate to obtain the electrolyte required for electrochemical reduction, and inject the electrolyte required for electrochemical reduction into the electrochemical oxidation tank for standby use.
[0210] (2) The raw carbon fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reaction at a potential difference of 0.5 V. After the reaction, it is washed with water and dried before being processed in stage ②.
[0211] Phase 2:
[0212] (1) Add 2644 g DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject 7 L toluene, and stir to fully dissolve DCPD; add a catalytic amount of methanesulfonic acid and stir evenly; dissolve 720 g (4-phenyl n-butyl) methyl sulfide in 3 L toluene and add dropwise to the reactor; heat to 180° C., react for 5 h, and cool to room temperature after the reaction is completed; filter to remove residue, wash the filtrate with water three times, and separate to obtain a mixed solution of the intermediate and component 2 in a molar ratio of 1:5;
[0213] (2) adding a catalytic amount of Raney Ni catalyst to the mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the pressure in the reactor at 0.2 MPa, heating to 60° C. for 15 h to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering and removing the residue after the reaction to obtain a mixed solution of component 1 and component 2 (hereinafter referred to as the stock solution);
[0214] (3) Add toluene to dilute the stock solution to a mass fraction of component 1 + component 2 of 60%, add deionized water and emulsifier twice the volume of the organic solution, and emulsify under stirring. The above emulsion, antistatic agent, lubricant and deionized water are prepared in a mass ratio of 20:0.5:0.8: the remainder (a total of 100) to form emulsion 1;
[0215] (4) dissolving dibenzoyl oxide + dimethylaniline in a molar ratio of 1:1 in toluene (mass fraction of 60%), adding deionized water and an emulsifier twice the volume of the organic solution, and preparing emulsion 2 under stirring (the oil-water ratio in emulsion 2 is 1:2, and the mass fraction of component 1 + component 2 is 20%);
[0216] (5) The carbon fiber is sized with emulsion 1 and then blown dry until no liquid drops fall, then sized with emulsion 2, then treated with ultraviolet light, and finally dried at 130°C and rolled up;
[0217] (6) The IFSS of carbon fiber and PDCPD after sizing is 23 MPa, and the IFSS of commercially sized CF and PDCDP is 12 MPa.
[0218] Embodiment 6:
[0219] Phase 1:
[0220] (1) 0.1 mM 2,6-di-tert-butyl-4-benzylidenecyclohexa-2,5-dienone was dissolved in toluene, and then 10 mM olefin derivative 6 of aniline (chemical structure as shown in Figure 6 As shown), stir until completely dissolved; dissolve 10mM nitrosoborate tetrafluoroborate in a minimum amount of toluene, then slowly drip into the above-mentioned olefin derivative 6 solution of aniline, react for 15 minutes, add 3mM tetrabutylammonium tetrafluoroborate to obtain the electrolyte required for electrochemical reduction, and inject the electrolyte required for electrochemical reduction into the electrochemical oxidation tank for standby use.
[0221] (2) The raw carbon fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reaction at a potential difference of 0.5 V. After the reaction, it is washed with water and dried before being processed in stage ②.
[0222] Phase 2:
[0223] (1) Add 2644 g of DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject 7 L of toluene, and stir to fully dissolve the DCPD; add a catalytic amount of methanesulfonic acid and stir evenly; dissolve 776 g of (5-phenyl-n-pentyl) methyl sulfide in 3 L of toluene and add dropwise to the reactor; heat to 180° C., react for 5 h, and cool to room temperature after the reaction is completed; filter to remove the residue, wash the filtrate with water three times, and separate the liquids to obtain a mixed solution of the intermediate and component 2 in a molar ratio of 1:5;
[0224] (2) adding a catalytic amount of Raney Ni catalyst to the mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the pressure in the reactor at 0.2 MPa, heating to 60° C. for 15 h to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering and removing the residue after the reaction to obtain a mixed solution of component 1 and component 2 (hereinafter referred to as the stock solution);
[0225] (3) Add toluene to dilute the stock solution to a mass fraction of component 1 + component 2 of 60%, add deionized water and emulsifier twice the volume of the organic solution, and emulsify under stirring. The above emulsion, antistatic agent, lubricant and deionized water are prepared in a mass ratio of 20:0.5:0.8: the remainder (a total of 100) to form emulsion 1;
[0226] (4) dissolving benzophenone oxide + azobisisobutyl cyanide in a molar ratio of 1:1 in toluene (mass fraction of 60%), adding deionized water and an emulsifier twice the volume of the organic solution, and preparing emulsion 2 under stirring (the oil-water ratio in emulsion 2 is 1:2, and the mass fraction of component 1 + component 2 is 20%);
[0227] (5) The carbon fiber is sized with emulsion 1 and then blown dry until no liquid drops fall, then sized with emulsion 2, then treated with ultraviolet light, and finally dried at 130°C and rolled up;
[0228] (6) The IFSS of carbon fiber and PDCPD after sizing is 23 MPa, and the IFSS of commercially sized CF and PDCDP is 12 MPa.
[0229] Embodiment 7:
[0230] Phase 1:
[0231] (1) 0.1 mM 2,6-di-tert-butyl-4-benzylidenecyclohexa-2,5-dienone was dissolved in toluene, and then 10 mM olefin derivative 7 of aniline (chemical structure as shown in Figure 7As shown), stir until completely dissolved; dissolve 10mM nitrosoborate tetrafluoroborate in a minimum amount of toluene, then slowly drip into the above-mentioned olefin derivative 7 solution of aniline, react for 15 minutes, add 3mM tetrabutylammonium tetrafluoroborate to obtain the electrolyte required for electrochemical reduction, and inject the electrolyte required for electrochemical reduction into the electrochemical oxidation tank for standby use.
[0232] (2) The raw carbon fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reaction at a potential difference of 0.5 V. After the reaction, it is washed with water and dried before being processed in stage ②.
[0233] Phase 2:
[0234] (1) Add 2644 g of DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject 7 L of toluene, and stir to fully dissolve the DCPD; add a catalytic amount of trifluoroacetic acid and stir evenly; dissolve 864 g of 1,3,5-tri(methylthio)benzene in 3 L of toluene and add dropwise to the reactor; heat to 180° C., react for 5 h, and cool to room temperature after the reaction is completed; filter to remove residue, wash the filtrate with water three times, and separate to obtain a mixed solution of component 1 and component 2 with a molar ratio of 1:5 (hereinafter referred to as the stock solution);
[0235] (2) adding a catalytic amount of Raney Ni catalyst to the mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the pressure in the reactor at 0.2 MPa, heating to 60° C. for 15 h to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering and removing the residue after the reaction to obtain a mixed solution of the intermediate and component 2;
[0236] (3) adding toluene to dilute the stock solution to a mass fraction of component 1 + component 2 of 20%, adding deionized water and an emulsifier equal in volume to the organic solution, and preparing emulsion 1 under stirring (the oil-water ratio in emulsion 1 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0237] (4) dissolving benzoin dimethyl ether in toluene (mass fraction of 20%), adding deionized water and emulsifier in an amount equal to the volume of the organic solution, and preparing emulsion 2 under stirring (the oil-water ratio in emulsion 2 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0238] (5) preparing a one-step emulsion sizing agent by mixing emulsion 1, emulsion 2, an antistatic agent, a lubricant and deionized water in a mass ratio of 5:0.5:0.1:0.2: the remainder (a total of 100);
[0239] (6) the carbon fiber is treated with ultraviolet light after being sizing agent prepared by the one-step emulsion sizing agent in step (4), and finally dried at 130° C. and rolled up;
[0240] (7) The IFSS of carbon fiber and PDCPD after sizing is 23 MPa, and the IFSS of commercially sized CF and PDCDP is 12 MPa.
[0241] Embodiment 8:
[0242] Phase 1:
[0243] (1) 0.1 mM 2,6-di-tert-butyl-4-benzylidenecyclohexa-2,5-dienone was dissolved in toluene, and then 10 mM olefin derivative 7 of aniline (chemical structure as shown in Figure 7 As shown), stir until completely dissolved; dissolve 10mM nitrosoborate tetrafluoroborate in a minimum amount of toluene, then slowly drip into the above-mentioned olefin derivative 7 solution of aniline, react for 15 minutes, add 3mM tetrabutylammonium tetrafluoroborate to obtain the electrolyte required for electrochemical reduction, and inject the electrolyte required for electrochemical reduction into the electrochemical oxidation tank for standby use.
[0244] (2) The raw carbon fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reaction at a potential difference of 0.5 V. After the reaction, it is washed with water and dried before being processed in stage ②.
[0245] Phase 2:
[0246] (1) Add 2644 g of DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject 7 L of toluene, and stir to fully dissolve the DCPD; add a catalytic amount of trifluoroacetic acid and stir evenly; dissolve 664 g of phenyl tert-butyl sulfide in 3 L of toluene and add dropwise to the reactor; heat to 180° C., react for 5 h, and cool to room temperature after the reaction is completed; filter to remove the residue, wash the filtrate with water three times, and separate the liquids to obtain a mixed solution of the intermediate and component 2 in a molar ratio of 1:5;
[0247] (2) adding a catalytic amount of Raney Ni catalyst to the mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the pressure in the reactor at 0.2 MPa, heating to 60° C. for 15 h to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering and removing the residue after the reaction to obtain a mixed solution of component 1 and component 2 (hereinafter referred to as the stock solution);
[0248] (3) adding toluene to dilute the stock solution to a mass fraction of component 1 + component 2 of 20%, adding deionized water and an emulsifier equal in volume to the organic solution, and preparing emulsion 1 under stirring (the oil-water ratio in emulsion 1 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0249] (4) dissolving benzoin dimethyl ether in toluene (mass fraction of 20%), adding deionized water and emulsifier in an amount equal to the volume of the organic solution, and preparing emulsion 2 under stirring (the oil-water ratio in emulsion 2 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0250] (5) preparing a one-step emulsion sizing agent by mixing emulsion 1, emulsion 2, an antistatic agent, a lubricant and deionized water in a mass ratio of 5:0.5:0.1:0.2: the remainder (a total of 100);
[0251] (6) the carbon fiber is treated with ultraviolet light after being sizing agent prepared by the one-step emulsion sizing agent in step (4), and finally dried at 130° C. and rolled up;
[0252] (7) The IFSS of carbon fiber and PDCPD after sizing is 23 MPa, and the IFSS of commercially sized CF and PDCDP is 12 MPa.
[0253] Embodiment 9:
[0254] Phase 1:
[0255] (1) 0.1 mM 2,6-di-tert-butyl-4-benzylidenecyclohexa-2,5-dienone was dissolved in toluene, and then 10 mM olefin derivative 7 of aniline (chemical structure as shown in Figure 7 As shown), stir until completely dissolved; dissolve 10mM nitrosoborate tetrafluoroborate in a minimum amount of toluene, then slowly drip into the above-mentioned olefin derivative 7 solution of aniline, react for 15 minutes, add 3mM tetrabutylammonium tetrafluoroborate to obtain the electrolyte required for electrochemical reduction, and inject the electrolyte required for electrochemical reduction into the electrochemical oxidation tank for standby use.
[0256] (2) The raw carbon fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reaction at a potential difference of 0.5 V. After the reaction, it is washed with water and dried before being processed in stage ②.
[0257] Phase 2:
[0258] (1) Add 2644 g of DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject 7 L of toluene, and stir to fully dissolve the DCPD; add a catalytic amount of trifluoroacetic acid and stir evenly; dissolve 664 g of phenyl tert-butyl sulfide in 3 L of toluene and add dropwise to the reactor; heat to 180° C., react for 5 h, and cool to room temperature after the reaction is completed; filter to remove the residue, wash the filtrate with water three times, and separate the liquids to obtain a mixed solution of the intermediate and component 2 in a molar ratio of 1:5;
[0259] (2) adding a catalytic amount of Raney Ni catalyst to the mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the pressure in the reactor at 0.2 MPa, heating to 60° C. for 15 h to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering and removing the residue after the reaction to obtain a mixed solution of component 1 and component 2 (hereinafter referred to as the stock solution);
[0260] (3) adding toluene to dilute the stock solution to a mass fraction of component 1 + component 2 of 20%, adding deionized water and an emulsifier equal in volume to the organic solution, and preparing emulsion 1 under stirring (the oil-water ratio in emulsion 1 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0261] (4) dissolving benzoin dimethyl ether in toluene (mass fraction of 20%), adding deionized water and emulsifier in an amount equal to the volume of the organic solution, and preparing emulsion 2 under stirring (the oil-water ratio in emulsion 2 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0262] (5) preparing a one-step emulsion sizing agent by mixing emulsion 1, emulsion 2, an antistatic agent, a lubricant and deionized water in a mass ratio of 5:0.5:0.1:0.2: the remainder (a total of 100);
[0263] (6) the carbon fiber is treated with ultraviolet light after being sizing agent prepared by the one-step emulsion sizing agent in step (4), and finally dried at 130° C. and rolled up;
[0264] (7) The IFSS of carbon fiber and PDCPD after sizing is 23 MPa, and the IFSS of commercially sized CF and PDCDP is 12 MPa.
[0265] Embodiment 10:
[0266] Phase 1:
[0267] (1) 0.1 mM 2,6-di-tert-butyl-4-benzylidenecyclohexa-2,5-dienone was dissolved in toluene, and then 10 mM olefin derivative 7 of aniline (chemical structure as shown in Figure 7 As shown), stir until completely dissolved; dissolve 10mM nitrosoborate tetrafluoroborate in a minimum amount of toluene, then slowly drip into the above-mentioned olefin derivative 7 solution of aniline, react for 15 minutes, add 3mM tetrabutylammonium tetrafluoroborate to obtain the electrolyte required for electrochemical reduction, and inject the electrolyte required for electrochemical reduction into the electrochemical oxidation tank for standby use.
[0268] (2) The raw carbon fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reaction at a potential difference of 0.5 V. After the reaction, it is washed with water and dried before being processed in stage ②.
[0269] Phase 2:
[0270] (1) Add 2644 g of DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject 7 L of toluene, and stir to fully dissolve the DCPD; add a catalytic amount of trifluoroacetic acid and stir evenly; dissolve 664 g of phenyl tert-butyl sulfide in 3 L of toluene and add dropwise to the reactor; heat to 180° C., react for 5 h, and cool to room temperature after the reaction is completed; filter to remove the residue, wash the filtrate with water three times, and separate the liquids to obtain a mixed solution of the intermediate and component 2 in a molar ratio of 1:5;
[0271] (2) adding a catalytic amount of Raney Ni catalyst to the mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the pressure in the reactor at 0.2 MPa, heating to 60° C. for 15 h to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering and removing the residue after the reaction to obtain a mixed solution of component 1 and component 2 (hereinafter referred to as the stock solution);
[0272] (3) adding toluene to dilute the stock solution to a mass fraction of component 1 + component 2 of 20%, adding deionized water and an emulsifier equal in volume to the organic solution, and preparing emulsion 1 under stirring (the oil-water ratio in emulsion 1 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0273] (4) dissolving benzoin dimethyl ether in toluene (mass fraction of 20%), adding deionized water and emulsifier in an amount equal to the volume of the organic solution, and preparing emulsion 2 under stirring (the oil-water ratio in emulsion 2 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0274] (5) preparing a one-step emulsion sizing agent by mixing emulsion 1, emulsion 2, an antistatic agent, a lubricant and deionized water in a mass ratio of 5:0.5:0.1:0.2: the remainder (a total of 100);
[0275] (6) the carbon fiber is treated with ultraviolet light after being sizing agent prepared by the one-step emulsion sizing agent in step (4), and finally dried at 130° C. and rolled up;
[0276] (7) The IFSS of carbon fiber and PDCPD after sizing is 23 MPa, and the IFSS of commercially sized CF and PDCDP is 12 MPa.
[0277] Embodiment 11:
[0278] Phase 1:
[0279] (1) 0.1 mM 2,6-di-tert-butyl-4-benzylidenecyclohexa-2,5-dienone was dissolved in toluene, and then 10 mM olefin derivative 7 of aniline (chemical structure as shown in Figure 7As shown), stir until completely dissolved; dissolve 10mM nitrosoborate tetrafluoroborate in a minimum amount of toluene, then slowly drip into the above-mentioned olefin derivative 7 solution of aniline, react for 15 minutes, add 3mM tetrabutylammonium tetrafluoroborate to obtain the electrolyte required for electrochemical reduction, and inject the electrolyte required for electrochemical reduction into the electrochemical oxidation tank for standby use.
[0280] (2) The raw carbon fiber (i.e., the original carbon fiber obtained by oxidation in an oxidation furnace) is introduced into an electrochemical oxidation tank as a cathode for electrochemical reaction at a potential difference of 0.5 V. After the reaction, it is washed with water and dried before being processed in stage ②.
[0281] Phase 2:
[0282] (1) Add 2644 g of DCPD to a reactor, seal the reactor, evacuate nitrogen three times, inject 7 L of toluene, and stir to fully dissolve the DCPD; add a catalytic amount of trifluoroacetic acid and stir evenly; dissolve 944 g of (5-phenyl-n-pentyl) tert-butyl sulfide in 3 L of toluene and add dropwise to the reactor; heat to 180° C., react for 5 h, and cool to room temperature after the reaction is completed; filter to remove the residue, wash the filtrate with water three times, and separate the liquids to obtain a mixed solution of the intermediate and component 2 in a molar ratio of 1:5;
[0283] (2) adding a catalytic amount of Raney Ni catalyst to the mixed solution of the intermediate and component 2, introducing hydrogen, sealing the reactor, maintaining the pressure in the reactor at 0.2 MPa, heating to 60° C. for 15 h to convert the sulfide functional group contained in the intermediate into a thiol functional group, filtering and removing the residue after the reaction to obtain a mixed solution of component 1 and component 2 (hereinafter referred to as the stock solution);
[0284] (3) adding toluene to dilute the stock solution to a mass fraction of component 1 + component 2 of 20%, adding deionized water and an emulsifier equal in volume to the organic solution, and preparing emulsion 1 under stirring (the oil-water ratio in emulsion 1 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0285] (4) dissolving benzoin dimethyl ether in toluene (mass fraction of 20%), adding deionized water and emulsifier in an amount equal to the volume of the organic solution, and preparing emulsion 2 under stirring (the oil-water ratio in emulsion 2 is 1:1, and the mass fraction of component 1 + component 2 is 10%);
[0286] (5) preparing a one-step emulsion sizing agent by mixing emulsion 1, emulsion 2, an antistatic agent, a lubricant and deionized water in a mass ratio of 5:0.5:0.1:0.2: the remainder (a total of 100);
[0287] (6) the carbon fiber is treated with ultraviolet light after being sizing agent prepared by the one-step emulsion sizing agent in step (4), and finally dried at 130° C. and rolled up;
[0288] (7) The IFSS of carbon fiber and PDCPD after sizing is 23 MPa, and the IFSS of commercially sized CF and PDCDP is 12 MPa.
[0289] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. An organic electrolyte used with (poly)dicyclopentadiene, characterized in that: Its structural formula is as follows: Wherein, R is one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures; n is any integer between 0 and 5; —H, —Ph.
2. The organic electrolyte according to claim 1, characterized in that The organic electrolyte is obtained by reacting an olefin derivative of aniline, nitrite tetrafluoroborate, an anti-crosslinking agent, and acetonitrile or toluene, and the synthesis reaction formula is as follows:
3. A carbon fiber surface treatment method, characterized in that: The following steps are involved: The carbon fiber surface treatment method is divided into two stages; Stage ① Olefin enrichment on carbon fiber surface: After carbonizing the carbon fiber, the surface is electrochemically treated; The electrochemical treatment process is as follows: the carbon fiber is used as the cathode, and the electrolyte required for electrochemical reduction includes an organic electrolyte and a supporting electrolyte; The organic electrolyte is obtained by reacting an olefin derivative of aniline, nitrite tetrafluoroborate, an anti-crosslinking agent, and acetonitrile or toluene, and the synthesis reaction formula is as follows: Wherein, R is one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures; n is any integer between 0 and 5; —H, —Ph Stage 2 Carbon fiber sizing: Sizing the electrochemically treated carbon fiber; The sizing agent required for the carbon fiber sizing treatment includes a coupling agent and a film-forming agent, wherein the coupling agent is recorded as component 1 and the film-forming agent is recorded as component 2; The sizing agent is synthesized simultaneously from dicyclopentadiene and a sulfide compound by a two-step method, and the reaction system is directly used to prepare a solution-type or emulsion-type sizing agent after filtration; The structural formula of the dicyclopentadiene is as follows: The structural formula of the thioether compound is as follows: Wherein, the three R1 groups are the same or different, and are one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures, and at least one of the three R1 is not a hydrogen atom; n1 is any integer between 0 and 5; —H、 The component 1 is a mixture of the following substances; Wherein, the three R2 groups are the same or different, and are one of the following structures, or one of the branched derivatives of the following structures, or one of the hyperbranched derivatives of the following structures, and at least one of the three R2 is not a hydrogen atom; n2 is any integer between 0 and 5 (including 0 and 5); —H、 The component 2 is a mixture of the following substances; The sizing agent further includes: a coupling catalyst, and the coupling catalyst is recorded as component 3.
4. The carbon fiber surface treatment method according to claim 3, characterized in that: The electrolyte required for electrochemical reduction is prepared by dissolving an anti-crosslinking agent in acetonitrile or toluene, then completely dissolving an olefin derivative of aniline in the acetonitrile or toluene solution of the anti-crosslinking agent, then dropping a saturated tetrafluoroborate nitrite solution into the above solution, reacting for 15 minutes, and finally dissolving a supporting electrolyte in the reaction system to obtain the electrolyte required for electrochemical reduction; The electrolyte required for electrochemical reduction: organic electrolyte molar concentration 1-10mM; The molar concentration of the supporting electrolyte is 1-3mM; the molar concentration of the anti-crosslinking agent is 0.01-0.1mM; The supporting electrolyte is tetrabutylammonium tetrafluoroborate; The anti-crosslinking agent is phenol, catechol, 2,4-dinitrophenol, 2,6-dinitro-p-cresol or 2,6-di-tert-butyl-4-benzylidenecyclohexa-2,5-dienone; The potential difference of the electrochemical reaction is 0.5V; The molar ratio of component 1 to component 2 in the sizing agent component is 1:0.8-1:
5.
5. The carbon fiber surface treatment method according to claim 3, characterized in that: In the first step of the reaction to obtain the sizing agent: The molar ratio of the reactant dicyclopentadiene to the sulfide compound is 2:1 to 5:1; The solvent is toluene, and the concentration of dicyclopentadiene is 0.1-2.0 mol / L; Catalyst 1 is aluminum chloride, aluminum bromide, trifluoroacetic acid or methanesulfonic acid; The reaction temperature is 60-200°C, and the synthesis reaction time is 2-7h.
6. The carbon fiber surface treatment method according to claim 3, characterized in that: In the second step of reaction to obtain the sizing agent: Catalyst 2 is Raney Ni; The reaction temperature is 40-60°C; The reaction time is 10-15h; The pressure of the reaction system is 0.1-0.2MPa.
7. The carbon fiber surface treatment method according to any one of claims 3 to 6, characterized in that: When component 3 requires high temperature initiation or light initiation, a one-step or two-step sizing method for carbon fiber surface treatment is adopted, or an emulsion sizing method or a solution sizing method is adopted; when component 3 requires room temperature initiation, a two-step emulsion sizing method for carbon fiber surface treatment is adopted.
8. The carbon fiber surface treatment method according to claim 7, characterized in that: Component 3 is dibenzoyl peroxide and dimethylaniline, or azobisisobutyl cyanide, or dibenzoyl peroxide, or benzoin dimethyl ether, or benzophenone and azobisisobutyl cyanide.
9. The carbon fiber surface treatment method according to claim 7, characterized in that: When component 3 is azobisisobutyl cyanide, dibenzoyl peroxide, dimethyl benzoate, or benzophenone and azobisisobutyl cyanide, a one-step emulsion sizing or one-step solution sizing carbon fiber surface treatment method is adopted; The above-mentioned one-step emulsion sizing carbon fiber surface treatment method specifically comprises the following steps: a. preparing a mixture of component 1 and component 2 into an emulsion, recorded as emulsion 1; b. preparing component 3 into an emulsion, recorded as emulsion 2; c. The emulsion 1, emulsion 2, antistatic agent, lubricant and deionized water in a mass ratio of 5 to 20: 0.5 to 10: 0.1 to 0.5: 0.2 to 0.8: the remainder, the remainder is the mass of deionized water, a total of 100 parts by mass, configured as an emulsion sizing agent; d. When component 3 is azobisisobutyl cyanide or dibenzoyl peroxide, the carbon fiber is sized and dried at 100-150°C before being rolled up; when component 3 is benzoin dimethyl ether or benzophenone and azobisisobutyl cyanide, the carbon fiber is first sized and then treated with ultraviolet rays, and then dried at 100-150°C before being rolled up; The above one-step solution sizing carbon fiber surface treatment method specifically comprises the following steps: a. The mixed solution of component 1 + component 2, component 3, antistatic agent, lubricant and organic solvent are configured as a solution-type sizing agent in a mass ratio of 1-2: 0.01-0.1: 0.1-0.5: 0.2-0.8: remainder, where the remainder is the mass of the organic solvent and the mass parts are 100 in total; b. When component 3 is azobisisobutyl cyanide or dibenzoyl peroxide, the carbon fiber is sizing and dried at 120-150°C before being rolled up; when component 3 is benzoin dimethyl ether or benzophenone and azobisisobutyl cyanide, the carbon fiber is first sizing and then treated with ultraviolet rays, and then dried at 120-150°C before being rolled up.
10. The carbon fiber surface treatment method according to claim 7, characterized in that: When component 3 is dibenzoyl peroxide and dimethylaniline, or azobisisobutyl cyanide, or dibenzoyl peroxide, or benzoin dimethyl ether, or benzophenone and azobisisobutyl cyanide, a two-step emulsion sizing method for treating the carbon fiber surface is used; The two-step emulsion sizing carbon fiber surface treatment method specifically comprises the following steps: a. preparing a mixture of component 1 and component 2 into an emulsion, recorded as emulsion 1; b. preparing component 3 into an emulsion, recorded as emulsion 2; c. The emulsion 1, antistatic agent, lubricant and deionized water in a mass ratio of: 5 to 20: 0.1 to 0.5: 0.2 to 0.8: the remainder, the remainder is the mass of deionized water, a total of 100 parts by mass, configured as an emulsion sizing agent; d. The carbon fiber is first sized with emulsion 2, and then blown dry until no liquid drops after sizing. The emulsion sizing obtained in step c, when component 3 is dibenzoyl peroxide and dimethylaniline, azobisisobutyl cyanide or dibenzoyl peroxide, the carbon fiber is sizing and then dried at 100-150°C and then rolled up; when component 3 is benzoin dimethyl ether or benzophenone and azobisisobutyl cyanide, the carbon fiber is first sizing and then treated with ultraviolet rays, and then dried at 100-150°C and then rolled up.
Citation Information
Patent Citations
Polydicyclopentadiene building template material and its preparation method
CN102827318A
Preparation process of glass fiber composite material
CN104448084A
Unsaturated polyester resin for improving ageing-resistant performance of anchoring agents
CN106366300A
High hardness and toughness modified unsaturated polyester resin and preparation method thereof
CN106589250A
High-toughness high temperature-resistant modified unsaturated polyester resin and preparation method thereof
CN106749947A